Analisis Peran Mediasi sebagai Upaya Perdamaian Praktik Peradilan Perdata - Anita; Annisa Raina Putri Ardhi; Anggi Sri Haryati Simarmata (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Mediation is an alternative method for resolving disputes, involving negotiations facilitated by an impartial third party known as a mediator. In the context of civil court practices in Indonesia, the process of mediation is governed by Supreme Court Regulation Number 1 of 2016 regarding Mediation Procedures in Court, which mandates that all civil cases at the first instance must undergo mediation prior to advancing to litigation. This study seeks to analyze the execution of dispute resolution via mediation in civil court practices and identify the elements that influence the effectiveness of mediation.The success of mediation in resolving civil disputes is influenced by several factors, including clear legal regulations, mediator professionalism, mediator certification, and the active role of the mediator in facilitating communication between the disputing parties. Effective mediation is expected to reduce case backlogs in courts and promote dispute resolution that is fast, simple, and cost-efficient.